2016
DOI: 10.1371/journal.pone.0148920
|View full text |Cite
|
Sign up to set email alerts
|

Ambulatory Blood Pressure Monitoring in Individuals with HIV: A Systematic Review and Meta-Analysis

Abstract: IntroductionAbnormal diurnal blood pressure (BP) rhythms may contribute to the high cardiovascular disease risk in HIV-positive (HIV+) individuals. To synthesize the current literature on ambulatory BP monitoring (ABPM) in HIV+ individuals, a systematic literature review and meta-analysis were performed.MethodsMedical databases were searched through November 11, 2015 for studies that reported ABPM results in HIV+ individuals. Data were extracted by 2 reviewers and pooled differences between HIV+ and HIV-negati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 54 publications
0
28
0
1
Order By: Relevance
“…7, 10, 18 In the Coronary Artery Risk Development in Young Adults (CARDIA) study (mean age = 30 years), nighttime SBP was 3.8 mmHg higher and the prevalence of non-dipping SBP was 2.44 times higher in African Americans compared with whites. 10 Several mechanisms may contribute to the higher prevalence of nocturnal hypertension and non-dipping BP among African Americans compared with whites.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…7, 10, 18 In the Coronary Artery Risk Development in Young Adults (CARDIA) study (mean age = 30 years), nighttime SBP was 3.8 mmHg higher and the prevalence of non-dipping SBP was 2.44 times higher in African Americans compared with whites. 10 Several mechanisms may contribute to the higher prevalence of nocturnal hypertension and non-dipping BP among African Americans compared with whites.…”
Section: Discussionmentioning
confidence: 99%
“…5, 32 A recent systematic review identified 8 studies that conducted ABPM in HIV+ individuals, 7 of which had HIV- comparison groups. 7 In a meta-analysis containing 5 of these studies, HIV+ individuals had 2.72 times higher odds of non-dipping SBP, compared with HIV- controls. 7 Of the 8 studies identified from the review, 7 of them consisted of European, mostly white individuals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An example of this includes individuals with HIV who have been shown to be at an increased risk for CV diseases (CVD), including hypertension. 42 Although studies of ABPM in HIV + individuals are limited, HIV + individuals have an increased prevalence of non-dipping BP 43 which may put them at increased risk for CV events. Identifying the factors associated with abnormal BP phenotypes within HIV + individuals would help elucidate the mechanisms underlying the excess CVD risk among this population and potentially identify new targets for intervention that can mitigate this excess risk.…”
Section: The Potential Applicability and Current Use Of Ambulatory Blmentioning
confidence: 99%